2019
DOI: 10.1002/cctc.201900331
|View full text |Cite
|
Sign up to set email alerts
|

Ni/La2O3 Catalysts for Dry Reforming of Methane: Insights into the Factors Improving the Catalytic Performance

Abstract: To understand the structure‐reactivity relationship of Ni/La2O3, and eventually get more applicable catalysts for DRM, glycine nitrate combustion (GNC), precipitation (PP) and thermal decomposition (TD) methods have been used to prepare La2O3 supports. Although all the supports possess a hexagonal La2O3 phase, their bulk and surface properties are significantly changed. By using them as supports, the interactions between NiO/Ni and La2O3 are varied, thus achieving Ni/La2O3 catalysts with different activity, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The desorption peaks below 400 C can be attributed to weakly basic sites, the peaks 400-600 C are assigned to basic sites of moderate strength, and the at temperatures higher than 600 C corresponds to strong basic sites. 42,43 The total amount of desorbed CO 2 is larger in Mg-Ni-La 2 O 3 compared to other catalysts, especially CO 2 desorbed from strong basic sites. This implies greater amount and enhanced strength of basic sites which can facilitate the adsorption and activation of CO 2 and enhance the DRM activity.…”
Section: Resultsmentioning
confidence: 97%
“…The desorption peaks below 400 C can be attributed to weakly basic sites, the peaks 400-600 C are assigned to basic sites of moderate strength, and the at temperatures higher than 600 C corresponds to strong basic sites. 42,43 The total amount of desorbed CO 2 is larger in Mg-Ni-La 2 O 3 compared to other catalysts, especially CO 2 desorbed from strong basic sites. This implies greater amount and enhanced strength of basic sites which can facilitate the adsorption and activation of CO 2 and enhance the DRM activity.…”
Section: Resultsmentioning
confidence: 97%
“…As La 2 O 3 can promote CO 2 adsorption and activation [33]; Ni/La 2 O 3 [34,35] and La 2 O 3 promoted Ni-based catalysts [36][37][38][39] have shown excellent activity in the DRM reaction. However, due to the low specific surface area of La 2 O 3 , the main problem with Ni/La 2 O 3 catalysts is the poor dispersion of Ni [40,41], leading to carbon deposition on Ni/La 2 O 3 catalysts [40,41]. Li et al [42] reported ordered mesoporous Ni/La 2 O 3 catalysts with large specific surface area for DRM, and the experimental result indicated that the increased interface between Ni and La 2 O 3 is beneficial for suppressing carbon deposition.…”
Section: Introductionmentioning
confidence: 99%
“…It is speculated that strong acid sites showed strong decomposition effects for C–C, C–H, and C–O. 34 A higher amount of strong acid sites on Ca-Ni-Al 2 O 3 and Co-Ni-Al 2 O 3 may lead to better catalytic performance. Additionally, medium acid sites were present on Ca-Ni-Al 2 O 3 and Co-Ni-Al 2 O 3 in the temperature range of 400–650 °C.…”
Section: Resultsmentioning
confidence: 99%